Factor VIIa Induced Release of von Willebrand Factor from Human Umbilical Vein Endothelial Cells by a Tyrosine Kinase Dependent Pathway - Brown, Simon A.; Bowen, Derrick J.; Hallett, Maurice B.; Giddings, John C.; Collins, Peter W. (Thrombosis and Haemostasis, 2002)
The interaction of FVIIa with surface-bound tissue factor (TF) induces various cellular changes including cytosolic Ca2+ signals. The release of von Willebrand factor (VWF) from endothelial cell stores may be triggered by an elevation in cytosolic free Ca2+, therefore we investigated the effect of rFVIIa on the release of VWF from human umbilical vein endothelial cells (HUVEC). We show here that rFVIIa induces the release of VWF from HUVEC with or without prestimulation with lipopolysaccharide (LPS). The effect of rFVIIa was dose dependent. However, the release of VWF by HUVEC in response to rFVIIa was significantly greater with LPS prestimulation (3.18 times control) than without LPS prestimulation (1.45 times control) (p <0.001). Cytosolic Ca2+ signals were detectable only after LPS prestimulation of HUVEC and these were small compared to those elicited by thrombin. No effect on rFVIIa induced release of VWF was seen in the presence of hirudin, site inactivated rFVIIa or the protein kinase C (PKC) inhibitor staurosporine. However, a tyrosine kinase inhibitor genistein, inhibited the rFVIIa induced release of VWF. These data show that release of VWF can occur without involvement of the cytosolic Ca2+/ PKC pathway. FVIIa induced VWF release from endothelial cells may have in vivo significance at sites of TF expression.
Keywords: Factor VIIa; von Willebrand factor; tyrosine kinase; human umbilical vein endothelium; calcium flux